2021
DOI: 10.21203/rs.3.rs-751838/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Location, Location, Location: A Discrete Choice Experiment to Inform Vaccination Programme Delivery in the UK

Abstract: BackgroundLarge-scale vaccination is fundamental to combatting COVID-19. In March 2021, the UK’s vaccination programme had delivered vaccines to large proportions of older and more vulnerable population groups; however, there was concern that uptake would be lower among young people. This research was designed to elicit the preferences of 18-29-year-olds with respect to key delivery characteristics.MethodsFrom 25 March - 2 April 2021, an online sample of 2,021 UK adults aged 18-29 years participated in a Discr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…There was mixed evidence for the effect of messengers on intention. An online DCE (pre-print) found that text message reminders were preferred if delivered by the NHS or one’s GP, rather than one’s best friend [ 39 ]. An online RCT (pre-print) found that a Republican endorsement of the vaccine through a video and short essay was more effective than a Democrat endorsement intentions among Republican or Republican leaning participants [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There was mixed evidence for the effect of messengers on intention. An online DCE (pre-print) found that text message reminders were preferred if delivered by the NHS or one’s GP, rather than one’s best friend [ 39 ]. An online RCT (pre-print) found that a Republican endorsement of the vaccine through a video and short essay was more effective than a Democrat endorsement intentions among Republican or Republican leaning participants [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…A DCE found that nearby GP surgeries were the most preferred vaccination location, whilst a nearby pharmacy and drive-thru were the least preferred [ 39 ]. Additionally, an online experiment found that more participants chose to receive their vaccine in 3 weeks at their local GP compared to in 5 days in a mass vaccination centre [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using data from 44 provinces in Thailand, Jarumaneeroj et al (2022) proposed a susceptible, infectious, quarantined, recovered, dead, vaccinated with immunity model that is later combined with a proposed COVID-19 vaccine allocation problem to determine the optimal allocation strategies that minimize total weighted strain on the whole healthcare system. Furthermore, a different contribution was presented by McPhedran et al (2021). They performed an online discrete choice experiment to understand population preferences to get vaccinated, considering four attributes: delivery mode, appointment timing, proximity, and SMS sender.…”
Section: Records and Analysismentioning
confidence: 99%